Anomalias na distribuição geográfica dos dados de saúde da bacia hidrográfica do Ribeirão Lindóia, zona norte do município de Londrina/PR - Paulo Rogério Araujo; José Paulo Peccinini Pinese (Confins)
Aiming at characterizing the geographic distribution of health data of Ribeirão Lindóia Basin, in Londrina City in Paraná, Brazil, correlating the possible patterns of hydro geochemical anomalies, geochemical parameters of water quality were analyzed through the Atomic Emission Spectrometry with Inductively Coupled Argon Plasma (SiO4-4, Fe3+, Zn2+, PO3-4, Al3+) and the Atomic Absorption Spectrometry (Na+ e K+). For Datasus information crossings and spatial organization of health data, the Philcarto software was used, highlighting Dengue fever, Viral Hepatitis and Meningitis attendance in the period from 2000 to 2004. For spatial analysis of regional data, the Surfer 8.0 software was used. It can be seen, more often, hydro geochemical anomalies, degraded water quality and high diagnosis of diseases in the UBS (Basic Health Unities/ Health Care Centers) in places where urbanization is exclusionary and unequal.